2016
DOI: 10.1108/nlw-08-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of open access electronic journals

Abstract: Biographical Details:Elizabeth Lightfoot is the electronic resources librarian and serials coordinator at Florida International University. She has a background in serials acquisitions, with primary interest in the management and sustainability of serials and e-resources. Structured Abstract:Purpose -Open access (OA) electronic journals have been identified as potentially at risk of loss without more coordinated preservation efforts. The purpose of this paper is to test the current availability of OA electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…At that time, the results of the research showed that access problems only affected 1.68% of the journals, proving DOAJ to be a valuable source of relevant primary sources. However, the results of a similar research carried in 2016 showed that around 5% of articles were unavailable using provided links, with another 25-26% of the articles being inaccessible if users were only able to obtain access through being redirected (Lightfoot, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…At that time, the results of the research showed that access problems only affected 1.68% of the journals, proving DOAJ to be a valuable source of relevant primary sources. However, the results of a similar research carried in 2016 showed that around 5% of articles were unavailable using provided links, with another 25-26% of the articles being inaccessible if users were only able to obtain access through being redirected (Lightfoot, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Especially small‐scale and APC‐free journals might have limited financial resources and, as a way to keep operating costs low, might opt for lightweight technical solutions, such as university websites and servers or content management systems like WordPress (Adema & Stone, 2017; Brown, 2013). However, these options do not protect against technical instabilities, and if the journals cannot afford to enroll in preservation schemes, long‐term access to their websites cannot be ensured (Lightfoot, 2016; Marchitelli, Galimberti, Bollini, & Mitchell, 2017). OA journals are enrolled in preservation schemes at an alarmingly low rate, with 4 in 10 journals indexed in the DOAJ reporting enrollment in at least one preservation or archiving scheme (5,881 out of 14,068 journals; DOAJ, 2019).…”
Section: Introductionmentioning
confidence: 99%